José Martínez Gázquez y Fernando González Muñoz, eds. 2022. Alchoran siue lex Saracenorum. Madrid: Consejo Superior de Investigaciones Científicas. 580 pp. ISBN 9788400110413 - Rivera Luque, José Luis Alexis (Estudios de Asia y África, 2024)
José Martínez Gázquez y Fernando González Muñoz, eds. 2022. Alchoran siue lex Saracenorum. Madrid: Consejo Superior de Investigaciones Científicas. 580 pp. ISBN 9788400110413